The Transformation of Religio-Cultural in Society Technology 5.0 Perspective Thought Alfin Toffler and Al-Ghazali - Nasrudin, Juhana (Addabani: Interdisciplinary Journal of Islamic Education, 2024)
Research related to integrating Toffler and Al-Ghazali’s thoughts aims to discover a conceptual framework that brings together these two complementary philosophies. This study is a literature review using a descriptive analysis approach. The research findings indicate that integrating Toffler and Al-Ghazali’s thinking results in understanding religio-cultural transformation in the era of technological civilization. Religio-cultural transformation in technological civilization is the outcome of a synthesis of these two philosophies. The integration yields several perspectives: First, understanding social and technological changes. Second,acculturation and adaptation. Third, ethics and morality of technology. Fourth, knowledge of culture and values. Fifth is cross-cultural understanding; sixth is tolerance and harmony. Therefore, integrating Alvin Toffler and Al-Ghazali’s thoughts in understanding religio-cultural transformation in the era of Technological Civilization can provide a holistic and balanced perspective. This will assist individuals, communities, and religious leaders address the challenges and opportunities arising in an increasingly connected and advanced technological society. Thus, this perspective can help create a diverse, tolerant, and ethical society in the Technological Civilization.